Descriptive statistics and risk assessment for the control of seasonal pollutant effects of 210Po and 210Pb in coastal waters (Canakkale, Turkey) - Akozcan, Serpil; Kulahci, Fatih (Springer, 2018)
Po-210 is absorbed into the human body by seafood intake. Especially, mollusks and mussels are known to have much higher Po-210 concentration than fish among various other types of seafood and are consumed in large quantities in Aegean Sea. Po-210 and Pb-210 radionuclide concentrations are obtained in the Mediterranean mussel (Mytilus galloprovincialis) and in the sediment samples collected from the Canakkale. The activity concentrations of Po-210 and Pb-210 are counted using alpha spectrometry. Activity concentrations of Po-210 and Pb-210 in mussels are in the ranged of 227 +/- 11-540 +/- 38 and 17 +/- 4-48 +/- 5 Bq kg(-1) dw (dry weight), for sediments the ranges are 23 +/- 6-41 +/- 3 and 15 +/- 3-44 +/- 1 Bq kg(-1) dw, respectively. Additionally, annual committed effective dose are calculated due to consumption mussel in Canakkale coastal region. The highest effective doses of Po-210 and Po-210 are found as 3187 and 56 mu Sv, respectively. Finally, risk analysis assessment is recommended to determine the pollutant effects of radionuclides. The risk fractions at the concentrations are easily determined with this evaluation process. This methodology has made a great contribution to risk assessments.
Keywords: Risk analysis; Po-210; Pb-210; Descriptive statistics; Mussel; Sediment; Annual dose